Factors affecting the frequency of citation of an article - Repiso, Rafael; Moreno-Delgado, Alicia; Aguaded, Ignacio (Iberoamerican Journal of Science Measurement and Communication, 2020)
The relevance of citations is clear since they constitute a substantial part of most bibliometric indicators. The aims of the present paper are to identify several factors associated with obtaining citations to explain these and, finally, to offer authors a number of useful suggestions. Those studies that have had the greatest influence on science are also those that are most frequently cited. The essential factor leading to a study being cited is that it should make a significant contribution to the advance of science; that is, the relevance of the research. But other essential dimensions exist: Accessibility; Dissemination; Scientific authority. Other predictive factors allow us to predict the number of citations a document may receive: Prior production by the authors; Structural context of the work; Scientific trends; Validity/Obsolescence (expiry) of results; Quality of formal aspects; Theoretical context of the study; Types of work. Finally, some ways are suggested to improve the citations of their works and thus contribute to a wider dissemination and development of science.